2018
DOI: 10.1177/0305735618754689
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between flow and music performance anxiety amongst professional classical orchestral musicians

Abstract: Research investigating methods of facilitating classical music performance has tended to focus on treating the debilitating effects of Music Performance Anxiety (MPA). It has been suggested that flow and MPA may be antithetical experiences and that fostering techniques for facilitating flow may provide a powerful tool for helping to alleviate MPA. However, there is a scarcity of data exploring professional classical musicians’ experiences of flow, and little empirical evidence supporting a relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 63 publications
8
72
0
4
Order By: Relevance
“…Physiologically, flow has been shown to share an inverted u-shaped relationship with stress-induced sympathetic arousal, and a positive linear relationship with parasympathetic heart rate control (Peifer et al, 2014 ). Cohen and Bodner ( 2018 ) observed a strong negative relationship between the occurrence of flow and performance anxiety among classical orchestral musicians, and suggest that devising means of encouraging flow might help reduce the effects of performance anxiety. Socially, some of the factors that support group flow, including joint attention (Wolf et al, 2015 ) and rhythmic synchronization (Hove and Risen, 2009 ), are also thought to underlie the heightened affiliation that has been shown to develop between musical partners.…”
Section: Research Directionsmentioning
confidence: 99%
“…Physiologically, flow has been shown to share an inverted u-shaped relationship with stress-induced sympathetic arousal, and a positive linear relationship with parasympathetic heart rate control (Peifer et al, 2014 ). Cohen and Bodner ( 2018 ) observed a strong negative relationship between the occurrence of flow and performance anxiety among classical orchestral musicians, and suggest that devising means of encouraging flow might help reduce the effects of performance anxiety. Socially, some of the factors that support group flow, including joint attention (Wolf et al, 2015 ) and rhythmic synchronization (Hove and Risen, 2009 ), are also thought to underlie the heightened affiliation that has been shown to develop between musical partners.…”
Section: Research Directionsmentioning
confidence: 99%
“…Anxiety is often described as having an antithetical relationship to the experience of flow (Csikszentmihalyi, 1975), and it has been suggested that fostering techniques for facilitating flow may provide a powerful tool for reducing MPA and encouraging optimal performance (Iusca, 2015;Lamont, 2012;Wrigley & Emmerson, 2011). Fullager et al (2013) found in their exploration of the relationship between MPA, flow and skill/challenge balance that: "when performance anxiety was highest, flow was lowest and vice versa … the presence of one minimises the magnitude of the other" (Fullager et al, 2013, p. 251), and a recent study found evidence of a strong, significant negative association between flow and MPA amongst 200 professional orchestral musicians (Cohen & Bodner, 2018), supporting Kirchner et al's (2008) earlier findings with music students. However, investigations of the clinical implications of the negative association between MPA and flow as a means of reducing MPA and facilitating flow, thereby encouraging optimal performance, have yet to be conducted.…”
Section: Music Performance Anxiety (Mpa)mentioning
confidence: 99%
“…Investigations of the efficacy of existing methods for treating MPA indicate that Cognitive Behavioural Therapy based interventions are most effective (for an overview, see Burin & Osorio, 2016). However, evidence suggests that pharmacological methods, particularly beta-blockers, are most commonly used, often in the absence of medical supervision (Cohen & Bodner, 2018;Kenny et al, 2014) and that the subject of MPA is still stigmatised, with many musicians and teachers unwilling to talk openly about it (Patston & Loughlan, 2014).…”
Section: Interventions For Improving Music Performancementioning
confidence: 99%
“…The difficulty of capturing flow is compounded in the psychological laboratory, where participants engage in what is typically an unfamiliar task in an inherently evaluative context. Both of these attributes -the unfamiliarity of the task and the evaluative nature of the context -are likely to work against the (already slim) likelihood of flow being experienced by a study participant, given that (1) flow appears more likely to be experienced by individuals who have developed considerable skill in the activity at hand (Jackson and Csikszentmihalyi, 1999;Rheinberg, 2008;Marin and Bhattacharya, 2013;Cohen and Bodner, 2019) and 2performance anxiety is not conducive to flow (Csikszentmihalyi, 1975;Fullagar et al, 2013).…”
Section: Continuous No Nomentioning
confidence: 99%
“…Appraisal theorists also agree that with increasing practice there is greater automatization of appraisal processes (Moors et al, 2013). This has particular relevance for flow because flow appears to be more commonly experienced by individuals who are quite skilled in the activity they are engaged in (and thus have logged many hours of practice) (Csikszentmihalyi, 1975;Dietrich, 2004;Marin and Bhattacharya, 2013;Cohen and Bodner, 2019). Therefore, it seems especially likely that any appraisal processes that may occur during flow are mostly or fully automatic.…”
Section: Source #1: Martin Seligmanmentioning
confidence: 99%